Spatiotemporal regulation of type I interferon expression determines the antiviral polarization of CD4+ T cells - De Giovanni, Marco; Cutillo, Valeria; Giladi, Amir; Sala, Eleonora; Maganuco, Carmela G.; Medaglia, Chiara; Di Lucia, Pietro; Bono, Elisa; Cristofani, Claudia; Consolo, Eleonora; Giustini, Leonardo; Fiore, Alessandra; et al. (Nature Immunology, 2020)
Differentiation of CD4+ T cells into either follicular helper T (TFH) or type 1 helper T (TH1) cells influences the balance between humoral and cellular adaptive immunity, but the mechanisms whereby pathogens elicit distinct effector cells are incompletely understood. Here we analyzed the spatiotemporal dynamics of CD4+ T cells during infection with recombinant vesicular stomatitis virus (VSV), which induces early, potent neutralizing antibodies, or recombinant lymphocytic choriomeningitis virus (LCMV), which induces a vigorous cellular response but inefficient neutralizing antibodies, expressing the same T cell epitope. Early exposure of dendritic cells to type I interferon (IFN), which occurred during infection with VSV, induced production of the cytokine IL-6 and drove TFH cell polarization, whereas late exposure to type I IFN, which occurred during infection with LCMV, did not induce IL-6 and allowed differentiation into TH1 cells. Thus, tight spatiotemporal regulation of type I IFN shapes antiviral CD4+ T cell differentiation and might instruct vaccine design strategies.
CRIS-Team Scopus Importer:2023-03-23